Ekstrak Buah Delima sebagai Alternatif Terapi Recurrent Apthous Stomatitis (RAS) - Sri Hernawati (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2015)
Recurrent aphthous stomatitis (RAS) is an oral mucosal lesion in the form of a single or multiple recurrent ulcer. The etiology is still not known, usually occurs in the second decade. RAS is more likely to strike in early adulthood with a tendency more often in women than men (3:1). The RAS precipitating factors are infection, trauma, hormones, emotional effect, fatigue, immunological disorders, nutritional disorders, and hereditary. Clinically RAS is in the form of ulcers that are round, single or multiple, varying in diameter, white-centered, redness in the edge, and painful. The RAS Classification: aphthous ulcers major, minor aphthous ulcers and herpetic form. Ulceration is a mucosal damage to the stratum basale, painful and interfere while chewing food. RAS can heal itself between 7-14 days and even more but the excruciating pain will torture the patient. Wound healing is a complex process that involves many elements which work in sync to achieve wound healing. Pomegranate is one of the widely studied medicinal plants for health. Pomegranate has benefits as anti-inflammatory, anti-oxidant, anti-microbial, immunostimulatory, cheap, easy to obtain, have no side effects. Pomegranate has very complex potential that can eliminate various predisposing factors in a single therapy and also can increase endurance. Based on this fact the purpose of this research is to theoretically study pomegranate as an alternative therapy for RAS biomolecularly. The conclusion is the active ingredient of pomegranate theoretically has the functions of anti-inflammatory, anti-oxidant, anti-microbial, immune-stimulatory and can regulate the fibrosis process, so that pomegranate can cure RAS.